Wittgensteinian Fideism vs. Classical Theism - Salvatore, Nicola Claudio; Oliveira da Silva, Rodrigo (Revista de Filosofía de la Universidad de Costa Rica, 2020)
<span style="color: #000000; font-family: ’Times New Roman’, serif; font-size: 16px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; text-align: justify; text-indent: 18px; text-transform: none; white-space: normal; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">In this paper, we will present and discuss Wittgenstein´s views on religious beliefs, in order to see if and to what extent they give a plausible account of religious belief and their epistemic status. In the first part of this work, we will present and discuss Wittgenstein´s views on the subject, while in the rest of the paper we aim to show that Wittgenstein´s treatment of religious belief might lead to a number of unpalatable conclusions.